2019
DOI: 10.3389/fped.2019.00491
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Associated With Advanced Liver Fibrosis Among Pediatric Patients With Non-alcoholic Fatty Liver Disease

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) among children is a growing concern with potential significant outcome. This study aims to investigate the relationship between hepatic steatosis, metabolic syndrome, and liver fibrosis among children with obesity and diabetes mellitus.Methodology: Children aged 6–18 years old were recruited from pediatric obesity and diabetes clinic in University Malaya Medical Center (UMMC) between year 2016 and 2019. Data on basic demographics, anthropometric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
2
17
1
Order By: Relevance
“…The same observation has been demonstrated in the adult population 3 . Importantly, this trend towards increased LSM in patients with diabetes may suggest early underlying and undetected fibrosis, as the metabolic syndrome has been associated with advanced liver fibrosis among paediatric NAFLD patients 39 . Our finding warrants further evaluation in larger cohorts.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The same observation has been demonstrated in the adult population 3 . Importantly, this trend towards increased LSM in patients with diabetes may suggest early underlying and undetected fibrosis, as the metabolic syndrome has been associated with advanced liver fibrosis among paediatric NAFLD patients 39 . Our finding warrants further evaluation in larger cohorts.…”
Section: Discussionsupporting
confidence: 84%
“…The same observation has been demonstrated in the adult population 3. Importantly, this trend towards increased LSM in patients with diabetes may suggest early underlying and undetected fibrosis, as the metabolic syndrome has been associated with advanced liver fibrosis among paediatric NAFLD patients 39. Our finding warrants further evaluation in larger cohorts.The impact of hepatic inflammation (as determined by an elevated ALT) on LSM is well described in the adult population40 and has recently become appreciated in the paediatric population, particularly in patients with minimal or no fibrosis at baseline 41.…”
supporting
confidence: 84%
“…Fujii et al showed that HOMA-IR and age are independent predictors of advanced fibrosis in patients with NAFLD but without T2DM [ 63 ]. In contrast, a cross-sectional study in children with obesity and diabetes mellitus showed that HOMA-IR is not an independent predictor of liver fibrosis assessed by LSM [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, metabolic components such as BMI, WC, systolic blood pressure (SBP), serum triglycerides (TG) levels, serum total cholesterol (TC) level, hemoglobin A1c (HbA1c), 2TDM, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were significantly higher in patients with liver fibrosis. Multivariate regression analysis shown that waist circumference is a significant independent predictor of liver fibrosis [ 46 ]. Analyses of one of the studies, which was conducted in a large cohort of obese adolescents (1278 participants), from 25 German, Austrian, and Swiss centers specializing in pediatric obesity, revealed that elevated waist circumference, as well as BMI, are strongly correlated to parameters of hepatocyte injury—ALT and gammaglutamyl transferase (GGT) [ 31 ].…”
Section: Pathogenetic Mechanisms Linking Nafld and Mets In Obese Cmentioning
confidence: 99%